Prevalence and factors associated with hospitalisation for bacterial skin infections among people who inject drugs: The ETHOS Engage Study. (1st August 2022) - Wheeler, Alice; Valerio, Heather; Cunningham, Evan B.; Martinello, Marianne; Barocas, Joshua A.; Colledge-Frisby, Samantha; Treloar, Carla; Amin, Janaki; Henderson, Charles; Read, Phillip; Matthews, Gail V.; Dunlop, Adrian J.; et al.
Abstract: Background: Injecting-related skin and soft tissue infections (SSTIs) are a preventable cause of inpatient hospitalisation among people who inject drugs (PWID). This study aimed to determine the prevalence of hospitalisation for SSTIs among PWID, and identify similarities and differences in factors associated with hospitalisation for SSTIs versus non-bacterial harms related to injecting drug use. Methods: We performed cross-sectional analyses of baseline data from an observational cohort study of PWID attending drug treatment clinics and needle and syringe programs in Australia. Logistic regression models were used to identify factors associated with self-reported hospitalisation for (1) SSTIs (abscess and/or cellulitis), and (2) non-bacterial harms related to injecting drug use (e.g., non-fatal overdose; hereafter referred to as non-bacterial harms ), both together and separately. Results: 1851 participants who injected drugs in the previous six months were enrolled (67% male; 85% injected in the past month; 42% receiving opioid agonist treatment [OAT]). In the previous year, 40% (n = 737) had been hospitalised for drug-related causes: 20% (n = 377) and 29% (n = 528) of participants were admitted to hospital for an SSTI and non-bacterial harm, respectively. Participants who were female (adjusted odds ratio [aOR]: 1.53, 95% CI: 1.19–1.97) or homeless (aOR: 1.59, 95% CI: 1.16–2.19) were more likely to be hospitalised for an SSTI, but not a non-bacterial harm. Both types of hospitalisation were more likely among people recently released from prison. Conclusions: Hospitalisation for SSTIs is common among PWID. Community-based interventions to prevent SSTIs and subsequent hospitalisation among PWID will require targeting of at-risk groups, including women, people experiencing homelessness, and incarcerated people upon prison release. Highlights: Hospitalisation for bacterial skin infections is common among people who inject drugs. Females, people experiencing homelessness, and people recently released from prison are at risk. Factors associated with hospitalisation for skin infections and other drug-related harms differ. Integration of wound care into harm reduction settings is needed.